Analisis Kinerja Pegawai di Dinas Pengelolaan Keuangan dan Aset Daerah Kota Semarang (Studi Kasus Bidang Aset Daerah) - Maria Mega Ayu Novrilia; Nina Widowati; Dyah Hariani (Journal of Public Policy and Management Review, 2014)
Performance is a resource management organization to achieve organizational goals. Good employee performance will directly affect the performance of the institution, and to improve employee performance certainly is a time consuming task and lengthy process.Department of Finance and Asset Management Semarang City or better known DPKAD Semarang, a new organization is the incorporation of Semarang Regional Revenue Office (Receipt) to Semarang Regional Secretariat Finance Department should have an employee who has a good performance in order to achieve the objectives established organizations , in this case remains that the goal ultimately is to provide a better public service again.Performance of employees in the Department of Finance and Asset Management Areas (DPKAD) Semarang is said not maximized because based on the dimensions that are used to analyze many problems. The dimensions that hinder the performance of employees in the Department of Finance and Asset Management Areas (DPKAD) Semarang is the quality of work, quantity of work, the use of time in work, and initiatives.